Combining synchrotron light with laser technology in catalysis research. (23rd August 2018) - Blomberg, Sara; Zetterberg, Johan; Gustafson, Johan; Zhou, Jianfeng; Shipilin, Mikhail; Pfaff, Sebastian; Hejral, Uta; Carlsson, Per-Anders; Gutowski, Olof; Bertram, Florian; Lundgren, Edvin
Abstract : High temporally and spatially resolved operando studies of CO oxidation using a Pd(100) single‐crystal surface as a model catalyst are presented. The surface structure is determined simultaneously as the gas phase is visualized in two dimensions in the vicinity of the catalyst surface. Abstract : High‐energy surface X‐ray diffraction (HESXRD) provides surface structural information with high temporal resolution, facilitating the understanding of the surface dynamics and structure of the active phase of catalytic surfaces. The surface structure detected during the reaction is sensitive to the composition of the gas phase close to the catalyst surface, and the catalytic activity of the sample itself may affect the surface structure, which in turn may complicate the assignment of the active phase. For this reason, planar laser‐induced fluorescence (PLIF) and HESXRD have been combined during the oxidation of CO over a Pd(100) crystal. PLIF complements the structural studies with an instantaneous two‐dimensional image of the CO2 gas phase in the vicinity of the active model catalyst. Here the combined HESXRD and PLIF operando measurements of CO oxidation over Pd(100) are presented, allowing for an improved assignment of the correlation between sample structure and the CO2 distribution above the sample surface with sub‐second time resolution.